The U.S. domestic intelligence enterprise history, development, and operations - Tromblay, Darren E. (CRC Press, Taylor & Francis Group, 2016)
This book takes a unique, in-depth approach that assesses not only the current state of affairs but also the evolution of the domestic intelligence enterprise. To accomplish this, it examines the origins and progress of the major agencies to show why they operate in the way that they do. By providing this perspective, the book promotes an understanding of the factors to consider when developing effective intelligence policy.